Mental Health in The Context of The COVID 19 Pandemic - Yadav Ravinder; Saini Varinder (International Journal of Coronaviruses, 2020)
We explore the global evidence of major health crisis potential impacts and the factors influencing the mental health outcomes among the population during the outbreak of COVID-19. Preparation measures for a COVID-19 focus on rapid quarantine of social isolation and economic concerns have risen metal health considerations that become an integrated part of the pandemic outbreak. This outbreak of novel Coronavirus disease (COVID-19) pandemic is swayed an overall 213 countries, areas or territories, with over 2,921,439 confirmed cases and 203,289 confirmed deaths reported till 26 April 2020. This created a lot of strain and fear; fear of falling ill and dying of being infected leading to heightened levels of insurmountable psychological pressure. This scrutiny attempt to assess the widespread outbreaks of COVID-19 on mental health professionals, healthcare workers and general population in association with adverse mental health sequelae like generalized anxiety disorder (GAD), depressive symptoms, insomnia, panic attacks, post-traumatic stress disorder, OCD, suicidal behavior, delirium, psychosis, harmful alcohol consumption, and drug use. There is a need for more evocative exploration to intensify awareness to address the potential psychological and behavioral risks that will remain elevated as long as the COVID-19 pandemic continues in the community. In conclusion, incessant surveillance of the subsyndromal mental health problems for outbreaks should be part of galvanized global action during the quarantine.
Keywords: Covid-19